1998
DOI: 10.1094/pdis.1998.82.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Control of Papaya Ringspot Virus-Type W in Zucchini Squash by Cross-Protection in Brazil

Abstract: Two mild strains of papaya ringspot virus-type W (PRSV-W) were tested under greenhouse and field conditions to study the potential of cross-protection for control of zucchini squash mosaic. Protected plants of zucchini squash cultivars Caserta and Clarinda were challenged with three severe strains from different geographic regions of the country in tests carried out in the greenhouse. Challenge inoculations were done mechanically 10 and 20 days after the protective inoculation. The mild strains did not have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
15

Year Published

1999
1999
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 20 publications
1
20
0
15
Order By: Relevance
“…Rating 1 was assigned to plants without mosaic symptoms and leaf deformations and with good development; rating 5 was assigned to those exhibiting mosaic symptoms, blisters, severe leaf deformations and plant stunting; ratings 2, 3 and 4 were assigned to intermediate symptoms between the two extremes (Rezende & Pacheco, 1998).…”
Section: Symptomatology and Biomass Evaluation Of Plants Infected Witmentioning
confidence: 99%
See 3 more Smart Citations
“…Rating 1 was assigned to plants without mosaic symptoms and leaf deformations and with good development; rating 5 was assigned to those exhibiting mosaic symptoms, blisters, severe leaf deformations and plant stunting; ratings 2, 3 and 4 were assigned to intermediate symptoms between the two extremes (Rezende & Pacheco, 1998).…”
Section: Symptomatology and Biomass Evaluation Of Plants Infected Witmentioning
confidence: 99%
“…In this case, the reduction in biomass was approximately 10 %. Field experiments have reported reductions of the order of 10 % as well, in total fruit yield of 'Caserta' zucchini squash and hybrid Tetsukabuto-type long-neck squash plants pre-immunized with strains PRSV-W-1 and PRSV-W-2 (Dias & Rezende, 2000;Rezende & Pacheco, 1998). Other authors have also reported yield decreases between 11 % and 15 % in plants pre-immunized by mild strains of other viruses, as Lecoq et al (1991) with ZYMV for zucchini squash and Montasser et al (1998) with CMV in melon.…”
Section: Symptomatology and Biomass In The Aerial Part Of Testplantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cross protection with mild strains of the virus has been tested with some success (Rezende and Pacheco 1998), but it needs further studies to be recommended to farmers, due to possible synergistic effect when the plants are infected by more than one virus. Genetic resistance is the ideal virus control strategy (Fraser 1992), both economically and environmentally.…”
Section: Introductionmentioning
confidence: 99%